УЛС ТӨРИЙН ФИЛОСОФИЙН СУДЛАХ ЗҮЙЛ, ХАМРАХ ХҮРЭЭ - Ч.Баатар, (Politology, 2023)
The latefs trends in resarch suggests that the resarch area and object - matter of political phylosophy cover the structrure and organization of society as wellas its jubect matters, developent and changes.